Pragmatics of Discourse - Schneider, Klaus P. (Handbooks of Pragmatics [HOPS], 2014)
Discourse is language as it occurs, in any form or context, beyond the speech act. It may be written or spoken, monological or dialogical, but there is always a communicative aim or purpose. The present volume provides systematic orientation in the vast field of studying discourse from a pragmatic perspective. It first gives an overview of a range of approaches developed for the analysis of discourse, including, among others, conversation analysis, genre analysis, functional discourse grammar and corpus-driven approaches. The focus is furthermore on functional units in discourse, such as disco